The Effect of Using Styrofoam As Additional Material For Asphalt Concrete Layer (Laston) – WC With BNA BLE - Arintha Indah Dwi Syafiarti; Fadlil Jalil Aslim; Gati Sri Utami; Ratih Sekartadji (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
Asphalt concrete layer (laston) has a high degree of flexibility so that placing it directly on top of layers such as AC-WC (Asphalt Concrete – Wearing Course) makes this layer vulnerable to damage due to high temperatures and heavy traffic loads. The type of damage that often occurs in the laston is the release of granules and cracks. Styrofoam is a type of plastic polymer that is thermoplastic when heated it becomes soft and hardens when cold. When mixed with gasoline, styrofoam will soften and can function as an adhesive. This study was to determine the value of Marshall characteristics in the addition of styrofoam into the asphalt.variations used for styrofoam content are 1%, 1.5%, 2% with asphalt content of 4.5%, 5.0%, 5.5%, 6.0%. The results showed that the optimum asphalt value was obtained at 6% asphalt content. And the mixture that meets the requirements is the addition of 1% styrofoam. Higher content of styrofoam will reduce the value of the melt (flow) and will reduce the value of Marshall stability.